Implementation of the Discovery Learning Model in Islamic Religious Education Learning to Build Students' Critical Thinking Awareness at SMAN 4, Bima City - Salaini; Sri Jamilah; Kaharuddin (Literasi: Jurnal Pendidikan Guru Indonesia, 2026)
This study aims to determine the implementation of the discovery learning model in Islamic Religious Education learning to build students’ critical thinking awareness at SMAN 4 Bima City. This research was motivated by the low level of student activeness and critical thinking skills in the learning process. The research method used was descriptive qualitative research with a field research approach. The results of the study showed that the implementation of the discovery learning model was able to improve students’ activeness, participation, and critical thinking skills in the learning process. Students became more enthusiastic in learning, more confident in expressing opinions, and more active in discussions and group collaboration. In its implementation, the teacher acted as a facilitator who provided stimulation in the form of questions and problems related to the learning material, so that students were encouraged to seek and discover concepts independently. The learning process through this model made learning more interactive, enjoyable, and student-centered (student centered learning). The supporting factors in the implementation of the discovery learning model included student activeness, the availability of learning media and resources, and a conducive learning environment. Meanwhile, the inhibiting factors included limited learning time and differences in students’ abilities in understanding the material. Therefore, it can be concluded that the discovery learning model is effective in Islamic Religious Education learning because it can improve students’ critical thinking awareness and create a more active and Learning resources and a conducive learning environment also became supporting factors